Water-soluble Dioxidovanadium(V) complexes of Aroylhydrazones: DNA/BSA interactions, hydrophobicity, and cell-selective anticancer potential - Sahu, G.; Banerjee, A.; Samanta, R.; Mohanthy, M.; Lima, S.; Tiekink, Edward R. T. *; Dinda, R. (American Chemical Society, 2021)
Five new anionic aqueous dioxidovanadium(V) complexes, [{VO2L1,2}A(H2O)n]α (1–5), with the aroylhydrazone ligands pyridine-4-carboxylic acid (3-ethoxy-2-hydroxybenzylidene)hydrazide (H2L1) and furan-2-carboxylic acid (3-ethoxy-2-hydroxybenzylidene)hydrazide (H2L2) incorporating different alkali metals (A = Na+, K+, Cs+) as countercation were synthesized and characterized by various physicochemical techniques. The solution-phase stabilities of 1–5 were determined by time-dependent NMR and UV–vis, and also the octanol/water partition coefficients were obtained by spectroscopic techniques. X-ray crystallography of 2–4 confirmed the presence of vanadium(V) centers coordinated by two cis-oxido-O atoms and the O, N, and O atoms of a dianionic tridentate ligand. To evaluate the biological behavior, all complexes were screened for their DNA/protein binding propensity through spectroscopic experiments. Finally, a cytotoxicity study of 1–5 was performed against colon (HT-29), breast (MCF-7), and cervical (HeLa) cancer cell lines and a noncancerous NIH-3T3 cell line. The cytotoxicity was cell-selective, being more active against HT-29 than against other cells. In addition, the role of hydrophobicity in the cytotoxicity was explained in that an optimal hydrophobicity is essential for high cytotoxicity. Moreover, the results of wound-healing assays indicated antimigration in case of HT-29 cells. Remarkably, 1 with an IC50 value of 5.42 ± 0.15 μM showed greater activity in comparison to cisplatin against the HT-29 cell line.